2004
DOI: 10.1111/j.1365-2966.2004.08278.x
|View full text |Cite
|
Sign up to set email alerts
|

Near-infraredK-band imaging of a sample of ultra-steep-spectrum radio sources selected at 74 MHz

Abstract: In this paper we present near-infrared K-band imaging of a sample of ultra-steep-spectrum (USS) radio sources selected at 74 MHz. The dual selection criteria of low frequency and USS mean that we should be sensitive to the highest-redshift (z > 5) radio galaxies. We have obtained K-band magnitudes for all of the objects in our sample of 26 and discuss the properties of each.There is a pronounced bias in this sample towards fainter magnitudes and thus higher redshifts when compared to complete unfiltered sample… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 28 publications
(40 reference statements)
0
11
0
Order By: Relevance
“…5 we show the K ‐band magnitude distribution of USS sources, measured in an 8‐arcsec diameter aperture. We compare our results with those obtained in the SUMSS–NVSS (De Breuck et al 2004), 6C** (Cruz et al 2007) catalogues and data selected at 74 MHz taken from Jarvis et al (2004). The mean K ‐band magnitudes in an 8‐arcsec diameter aperture of the USS is , which is 1 mag fainter than those obtained by De Breuck et al (2004) in the SUMSS–NVSS survey () and by Cruz et al (2006) in the 6C** survey ().…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…5 we show the K ‐band magnitude distribution of USS sources, measured in an 8‐arcsec diameter aperture. We compare our results with those obtained in the SUMSS–NVSS (De Breuck et al 2004), 6C** (Cruz et al 2007) catalogues and data selected at 74 MHz taken from Jarvis et al (2004). The mean K ‐band magnitudes in an 8‐arcsec diameter aperture of the USS is , which is 1 mag fainter than those obtained by De Breuck et al (2004) in the SUMSS–NVSS survey () and by Cruz et al (2006) in the 6C** survey ().…”
Section: Discussionmentioning
confidence: 69%
“…The vertical dashed line represent the expected K ‐band magnitude of a z ∼ 3 source, indicating that high‐redshift sources have compact radio morphologies. Several authors have applied the small angular size criterion in order to find high‐redshift radio galaxies (Blundell et al 1998; Jarvis et al 2004; Cruz et al 2006). There are a few cases of radio galaxies at high redshifts with large angular sizes (4C 23.56 at z = 2.483 has LAS = 53 arcsec).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has also been suggested that the SEDs of HzRGs will be intrinsically steeper thanks to enhanced inverse‐Compton (IC) losses of the relativistic electron population against the cosmic microwave background (CMB) photons whose energy density increases as (1 + z ) 4 (Krolik & Chen 1991). These two explanations have been adopted in the literature over recent years as the main contributors to the correlation (De Breuck et al 2000, 2002a; Pedani 2003; Cohen et al 2004; Jarvis et al 2004). The third explanation holds that the z –α correlation itself is indirect, reflecting an intrinsic correlation between radio luminosity and spectral index coupled to a Malmquist bias (Blundell, Rawlings & Willott 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Although an ultra-steep (radio) spectrum (USS; α −1 with S ∝ ν α ) does not guarantee a high redshift, and the USS selection may actually miss a large fraction of HzRGs (e.g. Waddington et al 1999;Jarvis et al 2001cJarvis et al , 2009), a higher fraction of high-redshift sources can be found among those with the steepest radio spectra, and most of the radio galaxies known at z > 3.5 have been found using the USS criterion (Blundell et al 1998;De Breuck et al 1998Jarvis et al 2001a,b;De Breuck et al 2002a;Jarvis et al 2004;Cruz et al 2006;Miley & De Breuck 2008). A satisfactory explanation for this trend is still missing.…”
Section: Introductionmentioning
confidence: 99%